Habituation of the Recitation of Ratib Al-Haddad, a Means of Improving the Character Education of Students (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Character education is needed in rebuilding a nation's civilization that has superior personality and character. Character education is currently very much needed and improved, given the fact that moral decadence is so massive that the causal factors range from the social environment, family, friends, social media, electronic media, and many more. Regarding this problem. TPQ Al-Ikhlas tries to apply the habit of reciting ratib al-haddad as a means of improving character education. Dhikr ratib al-haddad was chosen by the TPQ Al-Ikhlas institution because of its great benefits and virtues. With this dhikr, it is hoped that students will be equipped with the teachings of religious values, polite values, and ubudiyah divine values. The aims of this study were: (1) to find out the stages of habituating the remembrance of ratib al-haddad as a means of increasing the character education of TPQ Al-Ikhlas students (2) to find out the benefits of habituating the remembrance of ratib al-haddad for TPQ Al-Ikhlas students. In this study, a qualitative research method was used with a qualitative descriptive approach, in which the data collected was in the form of words, not in the form of numbers, so the preparation of the research report was composed of structured sentences. From the results of this study it can be seen that: (1) There are four stages of implementing the dhikr of ratib al-haddad carried out by the TPQ Al-Ikhlas institution as a means of improving character education for students, which consist of: the preparation stage, the initial stage, the implementation stage, namely by reading all series of remembrance of ratib al-haddad solemnly, and the final stage is by reading a prayer. (2) The benefits of practicing dhikr of ratib al-haddad for TPQ AL-Ikhlas students include: students become more polite, increase students' shy, queues become diligent, active in reciting the holy Qur’an, increase fluency in reading the Qur'an, and reduce students’ anger.